Downscaled CMIP6 future climate projections for New Zealand: climatology and extremes - Peter B. Gibson; Ashley M. Broadbent; Stephen J. Stuart; Hamish Lewis; Isaac Campbell; Neelesh Rampal; Luke J. Harrington; Jonny Williams (Weather and Climate Extremes, 2025)
Downscaled climate projections provide regionally relevant information for climate adaptation and planning purposes. Updated climate projections (∼12-km) are presented here for the New Zealand region, downscaling 6 global climate models (GCMs) from the Coupled Model Intercomparison Project (CMIP6) under a high emissions scenario (SSP3-7.0). Three regional climate models (RCMs) are used to explore differences when downscaling select GCMs. For end of century projections (relative to 1986–2005), the national multi-model annual mean warming is 3.1°C (model range 2.0–3.8°C) across downscaled simulations. Downscaling generally enhances warming over New Zealand relative to the GCMs, with the largest increases across high-elevation regions. There can be important differences in the projections across RCMs, including at national scales for temperature and across local-to-regional scales for precipitation. Averaged across models, annual extreme heatwaves become 3–5°C hotter for most regions. More frequent, intense, and longer duration meteorological drought is projected across northern and eastern regions of both islands. In terms of model uncertainty based on sign agreement, while summer mean precipitation projections carry the largest uncertainty, projections of summer meteorological drought and precipitation extremes can be made with greater confidence. These results provide a foundation for further targeted regional climate change impact and adaptation studies.